1977
DOI: 10.1002/ijc.2910200415
|View full text |Cite
|
Sign up to set email alerts
|

Two‐step chromosomal control of tumorigenicity of chinese hamster cells in nude mice

Abstract: A simple method for microinjecting isolated chromosomes into a single living cell under an inverted microscope has been developed. Of the 368 injected cells, 85 were able to form a colony and could be cloned. Clones of Chinese hamster V79 cells microinjected with chromosomes isolated from murine D56 cells [V79 (D56) cells] were tested for tumorigenicity in immunodeficient nude mice and for colony-forming ability in soft agar. Untreated recipient V79 cells were highly tumorigenic and had a high colony-forming a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
1984
1984

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Ebina et al (1975a) demonstrated that NCS prevents cultured mammalian cells from progressing through the cell cycle, resulting in the arrest of cell growth at the G2 or the G1-early S phases. They (Ebina and Ishida, 1975b;Ebina, Satake and Ishida, 1977) have shown that NCS inhibits cap formation in Daudi cells, cell spreading of HeLa cells and the vinblastine-induced paracrystal formation of tubulin, the subunit protein of the microtubules. NCS also affects the membrane-microfilament system in addition to the membrane-microtubule system (Yahara et al, 1979).…”
Section: Cell Cycle Mutantsmentioning
confidence: 99%
“…Ebina et al (1975a) demonstrated that NCS prevents cultured mammalian cells from progressing through the cell cycle, resulting in the arrest of cell growth at the G2 or the G1-early S phases. They (Ebina and Ishida, 1975b;Ebina, Satake and Ishida, 1977) have shown that NCS inhibits cap formation in Daudi cells, cell spreading of HeLa cells and the vinblastine-induced paracrystal formation of tubulin, the subunit protein of the microtubules. NCS also affects the membrane-microfilament system in addition to the membrane-microtubule system (Yahara et al, 1979).…”
Section: Cell Cycle Mutantsmentioning
confidence: 99%